Strategi Pengembangan Usaha (Studi Kasus pada Kedai Kopi Z Coffee & Roastery) - Nur Afdalia; Ahmad Effendi; Mustakim (Alkasb: Journal of Islamic Economics, 2023)
This article discusses the business development strategy of Z Coffee & Roastery Coffee Shop. Coffee shops have become a thriving industry in this area, with increasing competition. To win the competition and achieve sustainable growth, Z Coffee & Roastery needs to design an effective strategy. Business development strategies that can be carried out by Z Coffee Maros in an effort to increase sales are first, carrying out business efficiency, and carrying out hygiene standard certification which is used as one of the advantages when promoting cafes on social media, second, namely increasing cafe promotions and services as a whole, third, namely communicating the attractiveness of the menu to consumers, fourthly improving taste quality as well as menu appearance and innovating regularly on the menu, fifthly improving service quality and existence on social media.